Ethnobotany of Breadfruit in Vanuatu: Review and Prospects - Labouisse, Jean-Pierre (Ethnobiology Letters, 2016)
Breadfruit is a traditional staple crop and an important component of Pacific Island agrosystems. This article reviews documentation related to breadfruit in Vanuatu with a focus on ethnobotanical data recorded from the first contacts with European voyagers and missionaries to the most recent survey conducted on several islands in 2009. Tree management practices, food and non-food uses, conservation techniques, as well as ritual magic intended to increase yields and protect the crop, are described. A database of 539 cultivar names has been compiled. Some lines for future research within the social and biological sciences are proposed.